Assessing India’s Contribution to the Scholarly Publications of Asiatic Region - Dutta, Anirban; Jana, Sibsankar (Journal of Information and Knowledge, 2018)
This write-up represents the fundamentals of SCImago Journal and Country Ranking in terms of its scope, role in scientometrics study, and the important elements of different types of scientometrics indicators. It attempts to achieve some fundamental objectives of scientometrics, like: 1. ensure access to articles published in different R&D literature at national and global level, 2. reflect and represent true picture of scholarly contribution, research, scientific productivity at national and global level, and 3. have an authentic tool/ground for effective, efficient and rigorous evaluation of scholarly works. The SJR2 indicator takes into account not only the prestige of the citing scientific journal but also its closeness to the cited journal using the cosine of the angle between the vectors of the two journals’ co-citation. To eliminate the size effect, the accumulate prestige is divided by the fraction of the journal’s citable documents, thus eliminating the decreasing tendency of this type of indicator and giving meaning to the scores.